2019
DOI: 10.1242/dmm.042234
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms underlying Pax3-related neural tube defects and their prevention by folic acid

Abstract: Neural tube defects (NTDs), including spina bifida and anencephaly, are among the most common birth defects worldwide, but their underlying genetic and cellular causes are not well understood. Some NTDs are preventable by supplemental folic acid. However, despite widespread use of folic acid supplements and implementation of food fortification in many countries, the protective mechanism is unclear. Pax3 mutant (splotch; Sp2H) mice provide a model in which NTDs are preventable by folic acid and exacerbated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…An in vitro study demonstrated that folate receptors, which have TF function, regulate the expression of other TFs involved in neurodevelopment like Sox2 and Klf4 (kruppel like factor 4) (Mohanty et al, 2016). Interestingly, in a neural tube defect animal model based on the deletion of Pax3 , supplementation with folate restored the proliferative status of the neuroepithelium, demonstrating a possible common pathway regarding PAX3 and folate signaling (Sudiwala et al, 2019). Analysis of DNA methylation patterns in blood and tissue from the human umbilical cord demonstrated that folate deficiency during pregnancy is associated with methylation alterations in HOX, LIM, PAX, and TBOX TF families (Sakurai et al, 2019).…”
Section: Environmental Factors and Tfs In Psychiatric Disordersmentioning
confidence: 99%
“…An in vitro study demonstrated that folate receptors, which have TF function, regulate the expression of other TFs involved in neurodevelopment like Sox2 and Klf4 (kruppel like factor 4) (Mohanty et al, 2016). Interestingly, in a neural tube defect animal model based on the deletion of Pax3 , supplementation with folate restored the proliferative status of the neuroepithelium, demonstrating a possible common pathway regarding PAX3 and folate signaling (Sudiwala et al, 2019). Analysis of DNA methylation patterns in blood and tissue from the human umbilical cord demonstrated that folate deficiency during pregnancy is associated with methylation alterations in HOX, LIM, PAX, and TBOX TF families (Sakurai et al, 2019).…”
Section: Environmental Factors and Tfs In Psychiatric Disordersmentioning
confidence: 99%
“…Specifically for human therapies of the trunk and spine ( Figures 4 , 5 ), information arising from developmental neurotechnologies, including embryology, can now be analyzed to inform and improve treatments beyond trauma. Most recently, this includes neuromuscular disorders such as ALS and myasthenia gravis (reviewed in Sances et al, 2016 ; Faustino Martins et al, 2020 ), neural tube defects such as spina bifida that can be related to the Pax3 gene (Sudiwala et al, 2019 ), neurocristopathies such as Hirschsprung’s disease resulting from NCC migration defects (Fattahi et al, 2016 ; Workman et al, 2017 ), neurodegeneration or demyelinating process originating in the CNS (Garden and La Spada, 2012 ), and sensory disorders such as neuropathic pain (Manion et al, 2020 ). We expect that human stem cell developmental neurotechnologies will continue to play an essential role in understanding and treating these disorders through the elementary discovery of fundamental processes, in vitro models, and scalable high throughput platforms for drug testing, as well as by supplying an unlimited customized cell resource for replacement therapies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Sudiwala et al state that mutations in paired box 3 ( Pax3 ) gene lead to neural tube defects, Pax3 gene being responsible for neurulation to proceed. Supplements of folic acid restore proliferation in the cranial neuroepithelium, being state that the effect of folic acid to promote cell cycle compensates for the loss of Pax3 and therefore folic acid prevents cranial neural tube defects, such as anencephaly [ 26 ].…”
Section: ⧉ Etiopathogenesismentioning
confidence: 99%